An introduction to credit derivatives - Choudhry, Moorad (Fixed income markets library.)
In a relatively short time credit derivatives have grown to become one of the largest and most important segment of the financial markets, with deal volumes now in trillions of dollars. They have become an important tool for banks, financial institutions and corporates who desire greater flexibility in managing their credit risk and economic capital. This book is an accessible introduction to the various types of credit derivative instruments traded in the markets today. All products are described with the help of worked examples and Bloomberg screens, and the reader will be left with a thorou.